Expanding using the distributive property, we get (x-5)*(x-5)=x^2-5x-5x+25=x^2-10x+25. Multiplying that by -6, we get -6x^2+60x-150 . We then add 12 at the end to get -6x^2+60x-138. Using the quadratic formula (since we want the function to equal 0 to find the zeros), we get x=(-60+-sqrt(3600-3312))/(-6*2)=(-60+-sqrt(288))/-12. For sqrt(288), since 12^2=144 and 144*2=288, we can rewrite it as 12*sqrt(2). Putting that back in, we get
(-60+-(12*sqrt(2))/-12. Factoring it out, we get -5+-sqrt(2)=-5+sqrt(2) or -5-sqrt(2) which is C